2018
DOI: 10.1144/qjegh2017-143
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weathering-induced iron precipitation on properties of sandstone in a tropical environment

Abstract: Weathering-induced iron dissolution and precipitation in rock masses lead to reduction in shear strength of discontinuities, amongst others, while precipitation leads to an increase, and precipitated iron may reduce the susceptibility to future weathering. This effect is investigated in fieldwork campaigns with detailed rock mass characterization and chemical analyses in Kota Kinabalu, Malaysia. Many cut slopes in this area consist of different zones in which iron in various forms is either dissolved or precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Inversely, erosion causes the insulation to be removed, exposing the groundmass to the environment, accelerate weathering, and allow further progressive weathering in depth of new fresh ground. Erosion thus increases the rate of weathering of the underlying material (Huisman et al 2011;Tating et al 2019).…”
Section: Erosionmentioning
confidence: 99%
“…Inversely, erosion causes the insulation to be removed, exposing the groundmass to the environment, accelerate weathering, and allow further progressive weathering in depth of new fresh ground. Erosion thus increases the rate of weathering of the underlying material (Huisman et al 2011;Tating et al 2019).…”
Section: Erosionmentioning
confidence: 99%
“…In contrast, Ehlen (2002) studied the effects of the weathering process on the discontinuity properties of weathered granitic rocks and found no clear relation between the spacing and length of the discontinuities and weathering grades. A study on the effect of weathering on the properties of sandstone discontinuities (Tating et al, 2018) showed that the iron-oxide precipitation in the discontinuities reduces the susceptibility of sandstones to weathering and increases their shear strength. Although many previous studies have shown how the properties of main discontinuities contribute to rock mass quality, none of them have attempted to evaluate the contribution of other types of discontinuities, such as integral discontinuities, to rock mass quality and slope stability.…”
Section: Introductionmentioning
confidence: 99%
“…The thesis comprises of a collection of research papers submitted or published in peer review international journals and conferences (chapters 3 (Tating et al, 2013a;2013b;2013c); chapter 4 (Tating et al, 2015a); chapter 5 (Tating et al, 2015b)) with additionally an introduction, chapter on the description of the study area, and concluding chapter (chapters 1, 2 and 7). Chapter 6 describes the use of an exposure time parameter in the assessment of landslide susceptibility.…”
Section: Outline Of Thesismentioning
confidence: 99%
“…This chapter described the discontinuity development mechanism in thick to very thick bedded sandstone due to weathering and their implication in the engineering works on rock mass. This is based on the article "Weathering effects on discontinuity properties in sandstone in a tropical environment: Case Study at Kota Kinabalu, Sabah Malaysia" (Tating et al, 2015b).…”
Section: Chapter 4: Weathering Effect On Discontinuity Propertiesmentioning
confidence: 99%
See 1 more Smart Citation